Level of Religious Moderation of Students: Survey Analysis of Attitudes and Behavior / Tingkat Moderasi Beragama Mahasiswa: Analisis Survei Terhadap Sikap dan Perilaku - Sa'idah, Ishlakhatus; Amaliah Aryani; Akmalul Umam; Toifur (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
This study aims to examine the level of religious moderation among students of the Islamic Education Guidance and Counselling Study Program at IAIN Madura. Using a survey method, this study involved 151 students from the 2021–2024 intake who were selected through purposive random sampling. Data were collected using a religious moderation scale that measures dimensions such as national commitment, tolerance, anti-violence attitudes, and accommodation of local culture. The results of the analysis show that 60% of students have a moderate attitude in religion with high tolerance for differences of opinion. However, there are factors such as family background and previous educational experiences that influence this attitude. The conclusion of the study highlights that although the level of religious moderation is in a good position, challenges in accommodating local culture and commitment to nationality still need to be overcome. Therefore, strategic steps are needed, including the development of an integrative curriculum and the involvement of local communities, to improve religious moderation among students. These findings are expected to be a reference for further research in the field of religious moderation and education.